The geopolitical effects of migrant labor on Salah al-Din Governorate and its problems - Thahir Abdul Wahab Al-Janabi, Faisal Ali; Aswad Al-Ahbabi, Nassif Jassim (Journal of Tikrit University for Humanities, 2025)
This study discusses the impact and flow of expatriate workers on Iraq and their demographic, economic, and political effects. The study points out the cultural and social diversity in Iraq and how wars and conflicts led to internal and expatriate migrations that caused multiple infrastructure and economic challenges. The study shows how Salah al-Din Governorate, thanks to its geographical location and natural resources, is considered a center for attracting expatriate workers, which greatly affects the social fabric and local economy. The problem of the study revolves around the impact of geographical and political factors on the presence and distribution of expatriate workers in Iraq, especially in Salah al-Din Governorate, and how government institutions deal with the establishment of this workforce and the extent of its impact on national identity, in addition to the economic and social competitive challenges facing the local community. The study aims to analyze the impact of expatriate labor on Salah al-Din Governorate and the local labor force in Iraq in general, and to clarify the resulting economic and political impacts, including impacts on security and other political reasons, and to provide political and legal recommendations to deal with these challenges based on the collected data. The results highlighted that expatriate workers contribute significantly to enhancing economic growth by providing the skills and expertise necessary to implement major development projects. This labor supports the local economy by improving productivity and enhancing efficiency in various economic sectors, and the presence of expatriate workers enhances cultural diversity and enriches the social fabric. Despite the challenges associated with social integration, cultural and linguistic differences can be overcome through effective policies that promote understanding and coexistence between different cultures. In addition, the influx of expatriate workers leads to important demographic changes in Salah al-Din Governorate, which affects the demographic structure and creates new dynamics. It requires balanced policies to ensure sustainable development and social integration, and many proposals were made, including investing in improving and expanding infrastructure, such as roads, bridges, water and sewage networks, and health and educational facilities, to meet the increasing demand resulting from population growth and the presence of expatriate workers, and organizing programs which aims to seduce social tensions and enhancing social cohesion. These programs could include awareness campaigns and educational programs to promote understanding and cultural exchange between expatriate workers and local residents, in addition to establishing vocational training centers aimed at raising the efficiency of the local workforce, which reduces dependence on expatriate labor and enhances job opportunities for local citizens. Focusing on the technical and industrial skills needed in the market can contribute to achieving a greater balance between labor supply and demand.